The Safety of Single and Multilevel Cervical Total Disc Replacement in Ambulatory Surgery Centers - Cuéllar, Jason M; Lanman, Todd H; Rasouli, Alexandre (Spine (Philadelphia, Pa. 1976), 2020)
Retrospective cohort. Evaluate the safety profile of single- and multilevel cervical artificial disc replacement (ADR) performed in an outpatient setting. As healthcare costs rise, attempts are made to perform an increasing proportion of spine surgery in ambulatory surgery centers (ASCs). ASCs are more efficient, economically and functionally. Few studies have published on the safety profile of multilevel cervical ADR. We have performed an analysis of all consecutive cervical ADR surgeries that we performed in an ASC over a 9-month period, including multilevel and revision surgery. The pre-, intra-, and postoperative data recorded included age, sex, body mass index, tobacco use, and diabetes; level and procedure, operating room time, estimated blood loss (EBL), and complications; and discharge site, occurrence of reoperation, hospital admission, or any medical complication or infection over a 90-day period. A total of 147 patients underwent 231 treated levels: 71 single-level, 76 multilevel: 69 two-level, 6 three-level, and 1 four-level. Average age was 50 ± 10 years; 71 women, 76 men. None of the patients had insulin-dependent diabetes, 4 were current smokers, and 16 were former smokers. Average body mass index was 26.8 ± 4.6 (range 18-40). Average total anesthesia time was 88 minutes (range 39-168 min). Average EBL was 15 mL (range 5-100 mL). Approximately 90.3% of patients were discharged directly home, 9.7% to an aftercare facility. In the 90-day postoperative period there were zero deaths and two hospital admissions (1.4%)-one for medical complication (0.7%) and one for a surgical site infection (0.7%). In this consecutive case series we performed 231 ADRs in 147 patients in the outpatient setting, including multilevel and revision procedures, with 2 minor postoperative complications resulting in hospital unplanned admissions within 90 days. We believe that these procedures are safe to perform in an ASC. An efficient surgical team and careful patient selection criteria are critical in making this possible. 3.